1993
DOI: 10.1038/366033a0
|View full text |Cite
|
Sign up to set email alerts
|

The DNA replication fork can pass RNA polymerase without displacing the nascent transcript

Abstract: Replication proteins encoded by bacteriophage T4 generate DNA replication forks that can pass a molecule of Escherichia coli RNA polymerase moving in the same direction as the fork in vitro. The RNA polymerase ternary transcription complex remains bound to the DNA and retains a transcription bubble after the fork passes. The by-passed ternary complex can resume faithful RNA synthesis, suggesting that the multisubunit RNA polymerase of E. coli has evolved to retain its transcript after DNA replication, allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 40 publications
2
59
1
Order By: Relevance
“…The replication apparatus from T4 phage can bypass E. coli RNAP in head-on and codirectional orientations after pausing times of Ϸ1.7 sec and Ͻ1 sec, respectively (33,34). DNA polymerase from 29 can bypass B. subtilis RNAP during head-on encounters.…”
Section: Discussionmentioning
confidence: 99%
“…The replication apparatus from T4 phage can bypass E. coli RNAP in head-on and codirectional orientations after pausing times of Ϸ1.7 sec and Ͻ1 sec, respectively (33,34). DNA polymerase from 29 can bypass B. subtilis RNAP during head-on encounters.…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequences that have the potential to form secondary structures (Bedinger et al, 1989) or tracts of purines or pyrimidines in the DNA (Rao, 1994), have been shown to act as pausing sites during replication. Progression of the replication fork is also hampered during co-directional collisions with a transcription complex (French, 1992;Liu et al, 1993;Liu and Alberts, 1995;Elías-Arnanz and Salas, 1997). Under specific unfavourable growth conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we propose that after stalling at the lesion, the hybrid transiently dissociates to allow the DNA to move past the transcript during scrunching. This concept is adapted from the model of Liu et al (1993), who showed that an elongating E. coli transcription complex can continue transcription and generate a full-length RNA transcript after being bypassed by a DNA replication complex using the same template strand. The hybrid dissociation step is likely to require opening of the 'clamp' that closes on the hybrid in the elongation complex (Gnatt et al, 2001).…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…The proposed tethering protein is not shown. After incorporating U opposite the cyclo-dA lesion and stalling (A), the CM partially opens, allowing dissociation of the hybrid, but with retention of the nascent RNA (see Liu et al, 1993;B). Downstream DNA is pulled into the polymerase past the RNA transcript and extruded upstream by a scrunching mechanism (C).…”
Section: Speculations On the Role Of Csbmentioning
confidence: 99%